2002
DOI: 10.1021/bi015791b
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Escherichia coli Aminodeoxychorismate Synthase:  Architectural Conservation and Diversity in Chorismate-Utilizing Enzymes,

Abstract: Aminodeoxychorismate synthase is part of a heterodimeric complex that catalyzes the two-step biosynthesis of 4-amino-4-deoxychorismate, a precursor of p-aminobenzoate and folate in microorganisms. In the first step, a glutamine amidotransferase encoded by the pabA gene generates ammonia as a substrate that, along with chorismate, is used in the second step, catalyzed by aminodeoxychorismate synthase, the product of the pabB gene. Here we report the X-ray crystal structure of Escherichia coli PabB determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(125 citation statements)
references
References 39 publications
1
123
0
1
Order By: Relevance
“…The pyruvate lyase enzymes PabC and PchB are themselves not related and are proposed to work via quite distinct mechanisms: the former is a pyridoxal phosphate-containing enzyme related to amino acid aminotransferases (24), while the latter shows weak chorismate mutase activity and is related to AroQ-type chorismate mutases (17). It has been suggested that the presence of Lys274 in PabB may both influence the specificity of the reaction and predict the need for a separate lyase (39). Arguing against this being so, PchA has an alanine residue in the equivalent position, in common with the other lyase-competent enzymes TrpE, MbtI, and Irp9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pyruvate lyase enzymes PabC and PchB are themselves not related and are proposed to work via quite distinct mechanisms: the former is a pyridoxal phosphate-containing enzyme related to amino acid aminotransferases (24), while the latter shows weak chorismate mutase activity and is related to AroQ-type chorismate mutases (17). It has been suggested that the presence of Lys274 in PabB may both influence the specificity of the reaction and predict the need for a separate lyase (39). Arguing against this being so, PchA has an alanine residue in the equivalent position, in common with the other lyase-competent enzymes TrpE, MbtI, and Irp9.…”
Section: Discussionmentioning
confidence: 99%
“…However, His334 is on the mobile ␤16-␤17 loop and Thr271 on the adjacent ␤14 strand, so are both swung away from the active site in this "open" form; a ligand-binding role for these residues may be the major factor in loop closure. Adjacent to this part of the active site is Ala269, which is conserved as alanine in the Irp9 and TrpE enzymes but corresponds to Lys274 in PabB, where it has been proposed to discriminate between C-2 and C-4 substitution on chorismate substrates (39) and has recently been shown to be of critical importance for catalytic activity, as it forms a covalent intermediate during the reaction (3,4,27).…”
Section: Vol 188 2006 Structure Of Mbti From M Tuberculosis 6085 Tmentioning
confidence: 99%
See 2 more Smart Citations
“…In Escherichia coli, chorismate is converted via chorismate synthetase components I and II (PabB and PabA, EC 6.3.5.8) into 4-amino-4-deoxychorismate. Subsequently, pyruvate is cleaved by 4-amino-4-deoxychorismate lyase (PabC, EC 4.1.3.38), to result in pABA (10,26) (Fig. 1).…”
mentioning
confidence: 99%